2016
DOI: 10.1088/0031-9155/61/22/8120
|View full text |Cite
|
Sign up to set email alerts
|

A handheld SPIO-based sentinel lymph node mapping device using differential magnetometry

Abstract: Sentinel lymph node biopsy has become a staple tool in the diagnosis of breast cancer. By replacing the morbidity-plagued axillary node clearance with removing only those nodes most likely to contain metastases, it has greatly improved the quality of life of many breast cancer patients. However, due to the use of ionizing radiation emitted by the technetium-based tracer material, the current sentinel lymph node biopsy has serious drawbacks. Most urgently, the reliance on radioisotopes limits the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Meng et al (63) suggested that if MRI could accurately diagnose axillary lymph node metastases in early stage breast cancer, the most cost-effective strategy was to replace sentinel lymph node biopsy with axillary MRI. Detection of sentinel lymph nodes with SPIO can be done by a simple hand-hold probe ( Figure 3) (64)(65)(66)(67). A number of studies with the combination of Sienna plus ® and SentiMag ® (Endomagentics Ltd) have been reported.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
“…Meng et al (63) suggested that if MRI could accurately diagnose axillary lymph node metastases in early stage breast cancer, the most cost-effective strategy was to replace sentinel lymph node biopsy with axillary MRI. Detection of sentinel lymph nodes with SPIO can be done by a simple hand-hold probe ( Figure 3) (64)(65)(66)(67). A number of studies with the combination of Sienna plus ® and SentiMag ® (Endomagentics Ltd) have been reported.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
“…We should also note that, there are sensors with higher sensitivities, which work at room temperature, such as the giant magneto-resistance (GMR) and magneto-impedance (MI) sensors. However, these sensors do not work successfully in the vicinity of a magnet because their magnetic characteristics may change due to the nonuniformity of the strong magnetic field 28 , 29 .
Figure 2 Numerical results: ( a ) Two-dimensional distribution of the longitudinal magnetic field B Z of the permanent magnet.
…”
Section: Resultsmentioning
confidence: 99%
“…The other uses a permanent magnet for generating a direct magnetic field 19 (as demonstrated by M. Shiozawa et al .). The benefit of using an electromagnetic coil is that the strength of magnetic field can be adjusted and the nonlinear magnetic characteristics can be utilized 27 , 28 . However, the disadvantage of this method is that it requires a large power supply to generate strong magnetic fields, which in turn leads to the need for a countermeasure for Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the tracer will accumulate in the first nodes it encounters, namely, the sentinel nodes. The sentinel nodes can then be identified using a dedicated probe 6,7 and examined for metastases following surgical removal.…”
Section: Introductionmentioning
confidence: 99%
“…9 For in vivo SNB, a handheld probe is used. 7 Localization of SPIONs in vivo can also be useful in different applications, such as intraoperative assessment of tumor boundaries. 10 SPION detection can be optimized by matching the magnetic properties of the particle with the excitation parameters of the handheld probe.…”
Section: Introductionmentioning
confidence: 99%